Bim: the setback or solution to project cost issues in Malaysia construction industry? - Ang, P S E; Pung, Y L; Tsai, K L; Zulkaply, M NA; Tey, J S; Kasim, N B; Osman, M H; Musa, M K; Abdul Rahman, M A (2020)
Malaysia is progressing into Industry Revolution (IR) 4.0 which emphasizes more onto digital, data and artificial intelligence where everything is expected to be automated. However, cost tends to be a major issue at the pioneer stage of embracing technology where Building Information Modelling (BIM) for example tends to be a cost tussle for the current construction industry. Yet, research has shown that BIM is arguably one of the technology platforms in combating the costing issue considering that BIM enables 3D model elements to link to cost and auto-generate quantities which potentially achieve cost-effective project. Due to the conflicting perspectives of how BIM affects project cost issues, it is imperative to investigate the cost-related issues in implementing BIM in the project and to determine how BIM in general positively influences the overall project cost. Qualitative research is adopted in this study. A semi-structured interview was conducted among four professionals who employs BIM in their project. They consist of the assistant manager, senior manager and chief executive officer. The data collected is analysed by utilising Matrix Table for better organisation. The scope of the study is in the Selangor state in which the local construction industry had applied BIM in their construction industry up to the 3D stage. The results showed that the BIM implementation cost is not too burdensome as it is only a one-time cost and does not vary throughout the project period. In addition, the BIM influence on the overall cost of the project is beneficial to the industry. It improves workflow and cost management. In conclusion, BIM is beneficial to the construction industry in the long term. It is important to resolve the costrelated issues for implement BIM and hence, encourage the usage of BIM, especially in the IR 4.0 ecosystem